2021
DOI: 10.1177/00187208211010956
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Secondary Tasks on Police Officer Cognitive Workload and Performance Under Normal and Pursuit Driving Situations

Abstract: Objective The objective of this study was to assess the effects of single and multiple secondary tasks on officers’ performance and cognitive workload under normal and pursuit driving conditions. Background Motor vehicle crashes are a leading cause of police line of duty injuries and deaths. These crashes are mainly attributed to the use of in-vehicle technologies and multi-tasking while driving. Method Eighteen police officers participated in a driving simulation experiment. The experiment followed a within-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Prior studies using PCPS as a measure captured the baseline data before and after the completion of the study (Zahabi et al, 2021). However, in this study, we observed that the baselines collected before the data collection tended to be vastly larger than the baseline values collected at the end of the data collection.…”
Section: Limitations and Future Workmentioning
confidence: 62%
See 2 more Smart Citations
“…Prior studies using PCPS as a measure captured the baseline data before and after the completion of the study (Zahabi et al, 2021). However, in this study, we observed that the baselines collected before the data collection tended to be vastly larger than the baseline values collected at the end of the data collection.…”
Section: Limitations and Future Workmentioning
confidence: 62%
“…Higher positive values of PCPS are correlated to higher workload (Pfleging et al, 2016). A previous study on police officers with an average of 7.92 years of experience demonstrated average PCPS values of 10.99% in driving simulator tasks (Zahabi et al, 2021). What this means for the results is that the majority of nLEO participants had a similar or higher average PCPS during the ride-along compared to the average value for more experienced officers.…”
Section: Physiological Datamentioning
confidence: 72%
See 1 more Smart Citation
“…A carga de trabalho excessiva impacta, de forma significativa, os aspectos emocionais e cognitivos dos profissionais de segurança pública e das instituições policiais (Newell et al, 2022;Sherwood et al, 2019;Souza et al, 2012;Zahabi et al, 2023). A constante exposição a situações de alto risco, as longas jornadas de trabalha e a necessidade de tomar decisões rápidas 13 Artigos em contextos complexos e perigosos, contribuem para a exaustão emocional (Zahabi et al, 2023); bem como surgimento de sentimentos de frustração e impotência, trauma psicológico, aumento do risco de transtorno de ansiedade e transtorno depressivo, Síndrome de Burnout e alterações fisiológicas e do sono (Francisco et al, 2022;Ma et al, 2019;Souza et al, 2012).…”
Section: Introductionunclassified
“…Using simulators (if this could be assumed to be an equivalent learning activity to achieve a certain learning objective in police education) could increase teaching and practice opportunities (mass training); generate more individual feedback (pedagogical effect) on certain aspects of driving; and provide the opportunity to gradually increase the cognitive load (dual tasking such as communicating via radio, using GPS, etc.) in a safe environment (e.g., Gustavsson et al, 2020;Zahabi et al, 2021). Furthermore, researchers and instructors could gain increased knowledge about simulator-based training as a pedagogical tool, which could possibly lead to the development of police education in general and reduce the emissions this learning activity generates daily, one of Sweden's 16 environmental quality objectives in relation to Agenda 2030 (Naturvårdsverket, 2021).…”
Section: Introductionmentioning
confidence: 99%